PENGEMBANGAN MODEL LAYANAN PROGRAM USAHA KESEHATAN SEKOLAH (UKS) TERINTEGRASI PADA LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) DI KOTA SEMARANG (STUDI PADA LEMBAGA TAMAN KANAK-KANAK DI KOTA SEMARANG) - Mukminin, Amirul; Tasu’ah, Neneng (Jurnal Penelitian Pendidikan, 2016)
This research aims to know the service conductions, the mechanisms and forms of reporting, as well as to know the school health unit (UKS) program integrated to early childhood education (PAUD) institutions in the city of Semarang, in order for the service model development can run well. The objective of this research is to find out a service model of the school health unit integrated to the early childhood education institutions. This research belongs to development research. The samples were taken by using stratified random sampling technique, and data were analyzed in a descriptive analysis. This model was developed by modifying steps in learning activities at school. The research was able to describe (1) mechanisms of school health unit service program at early childhood education institutions, that includes triple UKS (health education, health services, fostering a healthy school environment), where most of its activities have not been conducted by related institutions, including the planning of activities; (2) mechanisms and the reporting form of UKS service program made by conducting team in the written form and reported to the headmaster, education service unit and community health center (Puskesmas); (3) UKS service program model integrated to early childhood education, in which conducting team identified and planned the activities of service programs on the institutions including triple UKS and determined in each daily lesson plans must be there the activities of UKS service programs in the beginning, in the middle, and also in the end of the activities.